2019
DOI: 10.1097/pts.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Culture of Safety and Rate of Adverse Events in Long-Term Care Facilities

Abstract: The aim of the study was to assess the relationship of culture of safety dimensions and the rate of unanticipated care outcomes in longterm care facilities (LTCFs) using the Agency for Healthcare Research and Quality framework of resident safety culture.Methods: Cross-sectional survey data were collected on 13 dimensions of culture of safety in five LTCFs from registered nurses, licensed practical nurses (LPNs), nursing assistants, administrators/managers, administrative support, and rehabilitation staff. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 22 publications
0
55
2
7
Order By: Relevance
“…Moreover, the relationship between patient safety culture and adverse events in nursing homes remains controversial. Some studies reported that an improvement in safety culture was associated with a decrease in rates of adverse events (Abusalem et al, 2019;Li et al, 2019), but no association found between them in a large national collaborative study (Smith et al, 2018…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the relationship between patient safety culture and adverse events in nursing homes remains controversial. Some studies reported that an improvement in safety culture was associated with a decrease in rates of adverse events (Abusalem et al, 2019;Li et al, 2019), but no association found between them in a large national collaborative study (Smith et al, 2018…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the literature on patient safety culture has focused on hospital settings, with relatively few studies conducted in nursing homes (Gartshore et al., 2017; Weaver et al., 2013). Quantitative surveys have been used in most studies conducted in the long‐term care facilities (Abusalem et al., 2019) or nursing homes (Desmedt, Petrovic, Beuckelaere, & Vandijck, 2018; Lin, Tseng, Hsu, Chiang, & Tseng, 2017; Ree & Wiig, 2019; Titlestad, Haugstvedt, Igland, & Graue, 2018). A few studies have reported on the relationship between patient safety culture and adverse events in nursing homes (Gartshore et al., 2017; Weaver et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Articles varied considerably in measuring safety culture with respect to instruments, mode of survey administration, timing relative to an intervention (e.g., baseline only or multiple measurements over time), unit of analysis (e.g., hospital-wide or ICU specific), and respondents (e.g., all staff vs only infection prevention leaders). Overall, 39 (70.9%) articles measured safety culture with a standardized tool such as the AHRQ Hospital Survey of Patient Safety Culture (HSOPSC) (n = 16) [47,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]; Nursing Home Survey on Patient Safety Culture (NHSPSC) (n = 2) [79,80]; the Safety Attitudes Questionnaire (SAQ) (n = 9) [62,[81][82][83][84][85][86][87]; the National Database of Nursing Quality Indicators (NDNQI) (n = 2) [74,88]; or qualitative methods (n = 4). Not all articles mentioned which safety culture domains were assessed, while some only assessed one domain of safety culture (e.g., teamwork) [78,84].…”
Section: Safety Culture Measurementmentioning
confidence: 99%
“…Nurse practitioners who often assume leadership functions claimed malpractice errors in public data gathered from the National Practitioner Data Bank (Sweeney et al, 2017). While the culture of safety is inversely proportional with the rate of errors in the clinical setting (Abusalem et al, 2019;Sholl et al, 2019), Kieft et al (2014) asserted the chief significance of quality of healthcare interventions to achieve a worthy patient experience, which a basic advocacy concept among nurses (Abbasinia et al, 2019). As the significant surgeon nurses' demands drastically ensued, the lack of appropriate education and experience is of considerable concern because professional competence constantly emanates from suitable knowledge and executive function (Feliciano et al, 2019;Sousa and Alves, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the 2015 Australian Council of Healthcare Standards (ACHS) Key Performance Indicators (KPIs) for patient safety outcomes include medication safety, infection control, pressure ulcer prevention, fall prevention, and blood management. As disputes on professionalism and safety culture persistently associate with alarming rates of hospital malpractice, a study came into a decision to undertake in determining the impact of these professional core competencies on the identified KPIs for patient safety outcomes (Abusalem et al, 2019;Sholl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%